Heavy training stress in male rowers: effects on circulatory responses and mood state profile - Purge, P.; Jürimäe, J.; Mäestu, J.; Jürimäe, T.; Karelson, K. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Rowing training is performed mainly as the extensive endurance type (Jurimae et al. 2001). For rowers, it has been demonstrated that the trained kilometers are positively related to the success in championships. However, the risk of overtraining increases with increasing daily training time and insufficient regeneration (Hooper et al. 1995; Jurimae et al. 2001). This means that it is important to identify specific parameters which could be used to monitor everyday training in order to avoid the overtraining syndrome in rowers. Therefore, the purpose of this investigation was to investigate whether a short-term overreaching state in rowers, as indicated by a decrease in performance parameters, is reflected in different circulatory and/or mood state parameters. Methods Fourteen national level rowers (18.6 +/- 2.0 yrs; 186.9 +/- 5.7 cm; 82.4 +/- 6.9 kg) were monitored over a six-day training camp. The training during the six-day training period amounted to 19.2 +/- 3.9 h, which was equivalent to an average increase in training volume by an approximately 100% compared with their average weekly training during the preceding four weeks. In total, 12 training sessions were completed during the overreaching training period compared to six training sessions during previous four weeks. Eighty five percent of the total training volume was low-intensity endurance training (rowing or running), 5% was high-intensity anaerobic training (rowing) and 10% was resistance training. Maximal 2000 m rowing ergometer test was performed on a wind resistance braked rowing ergometer (Concept II, Morrisville, USA). HR was measured continuously and stored at 5 s intervals during exercise tests by a sporttester Polar Vantage NV (Kempele, Finland). Expired gas was sampled continuously for the measurement of maximal oxygen consumption (VO2max; TrueMax 2400 Metabolic Measurement System, Parvo Medics, USA). Fingertip capillary blood (20 Mikro l) was sampled five minutes after the completion of the test. Blood lactate was determined from these samples enzymatically (Lange, Germany). A five milliliter blood sample was obtained from the antecubital vein with the subjects in the upright position. Red blood cell count, hemoglobin concentration, hematocrit and mean corpuscular volume (MCV) were measured. In addition, rowers were asked to record daily subjective ratings of quality of sleep, fatigue, stress and muscle soreness on a scale of one to seven from very, very low (point 1) to very, very high (point 7) (Hooper et al. 1995). Results 2000 m rowing ergometer performance time increased from 395.9 +/- 10.8 to 404.2 +/- 11.9 s corresponding to a mean power of 361.9 +/- 28.5 and 349.0 +/- 32.8 W, respectively. Blood lactate concentration measured five minutes after the test (from 19.2 +/- 2.9 to 16.2 +/- 2.3 mmol.l-1) and mean heart rate (from 184.6 +/- 7.5 to 179.2 +/- 7.4 beats.min-1) decreased. Maximal oxygen consumption remained unchanged. The subjective ratings of fatigue and muscle soreness increased and were related to the training volume (r>0.52). The blood parameters of red blood cell count, training period. The blood variables were not correlated with the training volume (r<-0.44; p>0.05). The change between tests in the mean heart rate demonstrated correlations to the changes in blood (r=-0.48) and plasma (r=-0.55) volumes. Discussion/Conclusion The reduced maximal performance in rowers was interpreted to reflect a state of fatigue or maybe overreaching. According to the results of the present study, the most appropriate and simple method for monitoring a short-term overreaching training period is self-analysis of mood states using daily training logs. Comprehensive physiological testing is less sensitive to dramatic increase in training volume of rowers. At present, it appears that self-analysis by the athlete who trains with high training loads is the most efficient method of monitoring possible short-term overreaching. Long term daily records of self-analysis can be kept with relative ease and compared with the more sophiscated physiological methods when necessary.